Longitudinal monitoring of mesoscopic cortical activity in a mouse model of microinfarcts reveals dissociations with behavioral and motor function. Issue 8 (August 2019) - Balbi, Matilde; Vanni, Matthieu P; Vega, Max J; Silasi, Gergely; Sekino, Yuki; Boyd, Jamie D; LeDue, Jeffrey M; Murphy, Timothy H
Small vessel disease is characterized by sporadic obstruction of small vessels leading to neuronal cell death. These microinfarcts often escape detection by conventional magnetic resonance imaging and are identified only upon postmortem examination. Our work explores a brain-wide microinfarct model in awake head-fixed mice, where occlusions of small penetrating arterioles are reproduced by endovascular injection of fluorescent microspheres. Mesoscopic functional connectivity was mapped longitudinally in awake GCaMP6 mice using genetically encoded calcium indicators for transcranial wide-field calcium imaging. Microsphere occlusions were quantified and changes in cerebral blood flow were measured with laser speckle imaging. The neurodeficit score in microinfarct mice was significantly higher than in sham, indicating impairment in motor function. The novel object recognition test showed a reduction in the discrimination index in microinfarct mice compared to sham. Graph-theoretic analysis of functional connectivity did not reveal significant differences in functional connectivity between sham and microinfarct mice. While behavioral tasks revealed impairments following microinfarct induction, the absence of measurable functional alterations in cortical activity has a less straightforward interpretation. The behavioral alterations produced by this model are consistent with alterations observed in human patients suffering from microinfarcts and support the validity of microsphere injection as a microinfarct model.